2020
DOI: 10.1097/mao.0000000000002688
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aging on the Electrically Evoked Compound Action Potential

Abstract: Objectives: To examine the effect of aging on electrically evoked compound action potential (eCAP) growth functions and their relationship with speech recognition in noise in cochlear implant (CI) users. Background: Aging typically leads to difficulty understanding speech in background noise. Previous research has explored cognitive and central auditory mechanisms contributing to these age-related changes. However, it is likely that the peripheral audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 58 publications
3
9
0
Order By: Relevance
“…Specifically, the middle-aged adults had significantly greater slopes than the elderly adults. This result is consistent with the previously reported age-related decline in slope of the eCAP AGF in the literature (Cafarelli Dees et al 2005; Jahn & Arenberg 2020b; Mussoi & Brown 2020; Shader et al 2020). Overall, these studies provide strong evidence that the slope of the eCAP AGF is negatively affected by advanced age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Specifically, the middle-aged adults had significantly greater slopes than the elderly adults. This result is consistent with the previously reported age-related decline in slope of the eCAP AGF in the literature (Cafarelli Dees et al 2005; Jahn & Arenberg 2020b; Mussoi & Brown 2020; Shader et al 2020). Overall, these studies provide strong evidence that the slope of the eCAP AGF is negatively affected by advanced age.…”
Section: Discussionsupporting
confidence: 93%
“…Reasons for this discrepancy in results between these studies remain unknown but may be related to the ages of participants included in the study and/or the number and locations of electrodes tested. Mussoi & Brown (2020) only recorded eCAP thresholds at one electrode location, while Cafarelli Dees et al (2005) and the present study recorded eCAP thresholds at three or more electrode locations. As observed in Figure 6, the differences in eCAP thresholds between the age groups varies across the electrode array.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Results of previously published studies have reported a significant aging effect on the slope of the eCAP input/output function (e.g., Mussoi & Brown 2020; Shader et al 2020) and on the sensitivity of the AN to amplitude modulation cues delivered using trains of biphasic pulses (Riggs et al 2021a). It should be pointed out that the single-pulse evoked eCAP results, as those measured for the eCAP input/output function, do not provide information about the effects of prior neural activity on response properties of the AN (e.g., Wilson et al 1997; Matsuoka et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As the aging process leads to SGN loss (11), findings from animal studies suggest that older age is associated with shallower eCAP AGF slopes, smaller eCAP amplitudes, and/or higher eCAP thresholds (12)(13)(14). In human CI users, studies also indicate that older recipients have shallower AGF slopes than their younger or middle-aged counterparts (15)(16)(17)(18)(19), with age at implantation being the most significant predictor of AGF slopes, although duration of deafness also has a significant effect on AGF slopes (20). However, findings across CI studies have been ambiguous on the effect of aging on eCAP maximum amplitudes (15,16) and on eCAP thresholds (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%